Tax policy, women and the law : UK and comparative perspectives - Mumford, Ann. (Cambridge [U.K.] ; New York, N.Y. : Cambridge University Press, 2010)
"Tax policy frequently targets the choices that women face in many aspects of their lives. Decisions regarding working away from home, having children, marrying, registering a partnership or cohabiting with a partner all entail tax consequences. The end of the twentieth century saw progress in women's legal and social equality, butmany governments began to increase their reliance on the tax system as a means of influencing the choices that women make. The juxtaposition of this instrumentalist deployment of tax with persisting economic inequality for women is the starting point for this book. Employing a range of theoretical approaches, and grounding its investigations in sociological theory and cultural philosophy, it provides the foundation for a comparative, contextual consideration of the issues that arise at the intersection of women, tax policy and the law"--Provided by publisher.
Introduction -- What is tax policy? -- Tax policy in action: gender budgeting -- Corporate social responsibility, and the possibility of common aims -- Tax policy in context -- Tax policy applied: taxation of the family unit -- Tax policy in systems revisited: families, tax law and the interaction of institutions -- Putting into the system: gender, markets and tax policy -- Conclusion.
Includes bibliographical references (pages 193-220) and index.
Keywords: Women -- Taxation; Women -- Taxation -- Law and legislation -- Great Britain; Women -- Economic conditions; Women -- Great Britain -- Economic conditions; Poor women; Fiscal policy -- Social aspects; Steuerrecht -- Frau -- Grossbritannien; Frau -- Steuerrecht -- Grossbritannien; Frau -- Steuerrecht -- Rechtsvergleichung; Steuerrecht -- Frau -- Rechtsvergleichung